The Added Value of Bio-Business Product Diversification of Nutmeg (Myristica Fragrans) in North Maluku Province - Palijama, Arnelia; Siti Jahroh; Juwita, Riskina (Jurnal Manajemen dan Agribisnis, 2024)
Background: Nutmeg (Myristica fragrans) is a native Indonesian plant that thrives in North Maluku Province. However, as one of the centers of nutmeg production, North Maluku is still lacking in carrying out nutmeg processing industry activities compared to other centers. Bio-business activities in the form of nutmeg product diversification have the potential to provide high economic value.Purpose: The objectives of this study are: first, to describe the nutmeg bio-business in North Maluku. Second, to analyze the added value obtained from the diversification of nutmeg products in North Maluku.Design/methodology/approach: The study was conducted from February to March 2024 in North Halmahera Regency and Ternate City, with a sample of 108 nutmeg farmers and 4 business actors. The study used a quantitative approach with a descriptive method from primary data. Furthermore, industrial trees were used in the study to provide an overview of the various types of products that can be produced from nutmeg commodities. Meanwhile, the Hayami method was used to determine the increase in added value from the diversification of nutmeg products.Finding/Result: The results of the study found that nutmeg bio-business activities in North Maluku Province resulted in product diversification from processed fruit skin, fruit flesh, seeds, and mace. Meanwhile, the highest added value of nutmeg product diversification in North Maluku is obtained from dried nutmeg seeds, nutmeg steam herbal medicine, nutmeg oil, and dried mace.Conclusion: The production of processed nutmeg products is still carried out as a home industry. There are nineteen (19) processed products that can be produced from nutmeg in North Maluku, as depicted in the industrial tree. The calculation of added value takes into account the proportion of nutmeg fruit to be processed products. Analysis of the added value of processed nutmeg products is carried out by calculating the added value per kilogram of nutmeg raw material for one production process.Originality/value (State of the art): This study is the first to analyze the added value of nutmeg bio-business product diversification in North Maluku Province. Keywords: Hayami method, home industry, industrial trees, nutmeg center, nutmeg processing